Transformation of Islamic Education Methods Through the Perspective of Philosophical Philosophy - Siti Machmudah Zainuri; Muhajir (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2026)
The transformation of Islamic educational methods through the perspective of philosophical thought that developed from classical to modern times by highlighting the contributions of figures such as Al-Farabi, Ibn Sina, and Al-Ghazali, this article identifies a significant change in educational approaches that are shifting from traditional methods that focus on memorization to a more holistic and critical approach. Al-Farabi emphasized the importance of character building and morality in education, while Ibn Sina introduced a scientific method that integrates observation and experimentation. Al-Ghazali, on the other hand, underlined the need for integration between science and spirituality. Through a thematic and interpretive analysis of these philosophical works, this article shows that the contribution of philosophical thought not only enriches the Islamic educational curriculum, but also creates a more adaptive and relevant educational system in an ever-evolving social and cultural context. These findings emphasize the importance of a balanced educational approach between intellectual and moral aspects in shaping individuals who are able to contribute positively to society.